2022
DOI: 10.3390/plants11030239
|View full text |Cite
|
Sign up to set email alerts
|

A Point Mutation in Phytochromobilin synthase Alters the Circadian Clock and Photoperiodic Flowering of Medicago truncatula

Abstract: Plants use seasonal cues to initiate flowering at an appropriate time of year to ensure optimal reproductive success. The circadian clock integrates these daily and seasonal cues with internal cues to initiate flowering. The molecular pathways that control the sensitivity of flowering to photoperiods (daylengths) are well described in the model plant Arabidopsis. However, much less is known for crop species, such as legumes. Here, we performed a flowering time screen of a TILLING population of Medicago truncat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 54 publications
0
1
0
Order By: Relevance
“…Nevertheless, progress has been made in identifying Medicago flowering-time regulators using forward and reverse genetics. These include the LD activators MtPHYTOCHROME A ( Jaudal et al., 2020b ), MtFE ( Thomson et al., 2021 ), and MtPHYTOCHROMOBILIN SYNTHASE ( Perez-Santangelo et al., 2022 ), and repressors MtCYCLING DOF FACTORS genes ( Zhang et al., 2019 ). The polycomb repressive complex 2 component MtVERNALISATION2 represses Medicago flowering until after vernalization ( Jaudal et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, progress has been made in identifying Medicago flowering-time regulators using forward and reverse genetics. These include the LD activators MtPHYTOCHROME A ( Jaudal et al., 2020b ), MtFE ( Thomson et al., 2021 ), and MtPHYTOCHROMOBILIN SYNTHASE ( Perez-Santangelo et al., 2022 ), and repressors MtCYCLING DOF FACTORS genes ( Zhang et al., 2019 ). The polycomb repressive complex 2 component MtVERNALISATION2 represses Medicago flowering until after vernalization ( Jaudal et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Kohchi et al (2001) initially reported the long-hypocotyl mutation of the HY2 gene encoding PΦB synthetase in Arabidopsis [10]. Subsequently, abnormal PΦB synthase function was reported in various other species, including the pcd2 mutant in pea (Pisum sativum L.) [11], the se13 mutant in rice (Oryza sativa L.) [12], the elh1 mutant in cucumber (Cucumis sativus L.) [13], the Gmlin1 mutant in soybean [14], and the Mtpφbs mutant in alfalfa (Medicago truncatula) [15]. Studies have shown that chromophore-deficient mutants generally have a light green or yellowish leaf phenotype, accompanied by a reduction in chlorophyll.…”
Section: Introductionmentioning
confidence: 99%